2016
DOI: 10.5005/jp-journals-10024-1959
|View full text |Cite
|
Sign up to set email alerts
|

A Clinicopathologic Study of Oral Changes in Gastroesophageal Reflux Disease, Gastritis, and Ulcerative Colitis

Abstract: Objectives The aim and objectives of this study are to identify oral changes in certain gastrointestinal (GI) diseases, namely gastroesophageal reflux disease (GERD), ulcerative colitis, gastritis, and to evaluate these oral symptoms as indicators for assessing GI disorders. Materials and methods In this study, the oral manifestations of various GI disorders were assessed in a varying age group of 250 patients in Government Stanley Medical College and Hospital, Chennai. Out of 250 patients, 142 were affected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Initial screening identified 386 papers. Among these papers, 22 articles met our inclusion criteria and were kept for analysis (Fig 1, Table 2) [11][12][13][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41]. Two additional basic research studies were included.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Initial screening identified 386 papers. Among these papers, 22 articles met our inclusion criteria and were kept for analysis (Fig 1, Table 2) [11][12][13][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41]. Two additional basic research studies were included.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, Vinesh et al reported a periodontitis rate of 25.5% in GERD patients [39]. In the same study, the authors reported that <10% of GERD patients had oral mucosa or gingival inflammation findings (erythema, ulcer) [39]. These results did not corroborate those of Yoshikawa et al and Watanabe et al who reported more frequently mucosa inflammatory findings (papillary, marginal, attached index) in GERD patients compared with controls [11,34].…”
Section: Plos Onementioning
confidence: 87%
See 3 more Smart Citations